Meningkatkan Pemahaman Siswa Terhadap Materi Ciri-Ciri Dan Kebutuhan Mahluk Hidup Dengan Menggunakan Media Lingkungan Sekitar Pada Mata Pelajaran IPA Kelas VI SDN 1 Sukadana - Dayang Rahimah (Journal Innovation In Education, 2023)
We understand that learning media is currently developing rapidly, but due to the limitations of SDN 1 Sukadana, class teachers at the school must be very clever in utilizing the facilities around the school to make learning more interesting. However, not all teachers are able to utilize the facilities around the school for the teaching and learning process and they tend to never be used in classroom learning.The author experienced the learning process by tryingseveral existing methods. Learning lacks enthusiasm in learning, some chat, daydream and remain silent. From the formative test carried out by the author at the end of the lesson, the results can be seen. The majority (70%) of students got a score below the specified KKM, namely 70.Researchers offer alternative problem solving by implementing learning using environmental media around the school. It is hoped that by not always being in class and seeing the environment around them, students will not feel bored and fed up with the media they have been using so far.After going through research carried out in 2 cycles of classroom action, there was an increase in attention to learning following improved learning using environmental media in the science subject material on the characteristics and needs of living things by 42.5%, namely before the research it was 50% and after the second cycle. There was research on learning achievement after taking part in learning improvement action research using environmental media in the science subject material on the characteristics and needs of living things, amounting to 67%. Before the research there were 4 students (20% who got a score of 65 and after the research this increased to 19 students 95%)